Single-cell profiling of the antigen-specific response to BNT162b2 SARS-CoV-2 RNA vaccine - Kevin J. Kramer; Erin M. Wilfong; Kelsey Voss; Sierra M. Barone; Andrea R. Shiakolas; Nagarajan Raju; Caroline E. Roe; Naveenchandra Suryadevara; Lauren M. Walker; Steven C. Wall; Ariana Paulo; Samuel Schaefer; et al. (Nature Communications, 2022)
Vaccination against COVID-19 has shown activation of different immune cell types. Here the authors characterise the immune response to the SARS-CoV-2 mRNA vaccine using longitudinal CyTOF single cell approaches to characterise antigen specific B and T-cell responses promoted by this vaccine.